2015
DOI: 10.1542/peds.2014-2777
|View full text |Cite
|
Sign up to set email alerts
|

BMI Curves for Preterm Infants

Abstract: BACKGROUND AND OBJECTIVES: Preterm infants experience disproportionate growth failure postnatally and may be large weight for length despite being small weight for age by hospital discharge. The objective of this study was to create and validate intrauterine weight-for-length growth curves using the contemporary, large, racially diverse US birth parameters sample used to create the Olsen weight-, length-, and head-circumference-for-age curves.METHODS: Data from 391 681 US infants (Pediatrix Medical Group) born… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 54 publications
1
99
0
2
Order By: Relevance
“…Body mass index (BMI) has been widely used for nutritional assessment and adiposity in children however underutilized in neonates. 5 This was partly due to lack of reference standards for different gestational ages. Olsen et al published reference BMI curves in 2015 and concluded that disproportionate growth failure in infants is best detected by gender specific BMI for age percentile curves when compared size for age methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Body mass index (BMI) has been widely used for nutritional assessment and adiposity in children however underutilized in neonates. 5 This was partly due to lack of reference standards for different gestational ages. Olsen et al published reference BMI curves in 2015 and concluded that disproportionate growth failure in infants is best detected by gender specific BMI for age percentile curves when compared size for age methods.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the body mass index was calculated using the formula: weight in kilograms/ length in metre 2 and plotted on the gender specific BMI charts by Olsen et al 5 BMI less than tenth percentile was considered as fetal undernutrition. Then, neonates were classified into appropriate for gestational age (AGA) if their birth weights ranged between 10 th and 90 th centiles for that gestational age, small for gestational age (SGA) if their weights fell below 10 th centile or large for gestational age (LGA) if their weights were more than 90 th centile on the various intra uterine growth charts.…”
Section: Nutritional Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…As pointed out in the recent article by Olsen et al, 1 the appropriate growth of a prematurely born infant may have a significant impact on his or her developmental and growth outcomes after discharge from the NICU. In fact, appropriate growth encompasses many aspects of the care of the premature infant besides the monitoring of growth parameters and providing appropriate fortified nutrition.…”
mentioning
confidence: 99%